Study of Students' Interests and Attitudes in Science: SMP and Madrasah Tsanawiyah - Retni Sulistiyoning Budiarti; Dwi Agus Kurniawan; Yulita Dwi Citra; Fhadira Insani Putri; Sabila Eka Septi (Mimbar Ilmu, 2023)
Interests and attitudes play an important role in the development of students in the learning process, so research is needed to discuss these two variables. This study aims to analyze the relationship between students' interests and attitudes and to find out the differences in students' interests and attitudes in two schools at the secondary school level. This research method uses quantitative research with survey research procedures. The data collection technique in this study used an interest and attitude questionnaire instrument that an expert validator had validated. The data analysis technique used in this research is descriptive statistical analysis test and inferential statistical analysis test. The sampling technique is random sampling. The total number of samples is 152 samples. The research results show a relationship between the interests and attitudes of students at SMPN. There is a relationship between the interests and attitudes of students at MTsN, and there are differences in the interests and attitudes of students at SMPN and MTsN. It was concluded that students' interests and attitudes were interconnected in the two schools, and there were differences in students' interests and attitudes between public schools and madrasah-based schools.